A Stylistic Analysis of German Advertisements - Yosefa Ananda Elizabeth Sidabutar; Surya Masniari Hutagalung (Future Science, 2024)
This research aims to find out which language styles and how to analyze the stylistics that exist in the German advertisements of Nike, Coca-Cola, the North Face, and Porsche. This research is qualitative and descriptive and helps German teachers and students to understand the stylistics. The data in this research are words, sentences, dialogues, or conversations that contain language styles in German advertisements of Nike, Coca-Cola, the North Face, and Porsche. According to Kulmbach's theory, 48 out of 80 sentences in the four advertisements were identified as language styles. The most frequently used language style in these advertisements is the comparative language style, but the repetition, contradiction, and conjunctive language styles can also be found in some sentences. The comparative language style essentially compares two different things that are deliberately seen as the same thing. This research has been validated by an expert and the results of this analysis are accurate.